KINERJA PEMERINTAH DALAM MENINGKATKAN KUALITAS PEMBANGUNAN PARIWISATA DI KOTA BANYUWANGI - Idrus, Iqbal Aidar; Ferdian, Komang Jaka; Cahyani, Asya Putri (Program Studi Ilmu Pemeritahan Fakultas Ilmu sosial dan Ilmu Politik Universitas 17 Agustu, 2018)
Development in the region can be seen with the development in the field of tourism because tourism is a mainstay sector that can be a source of revenue for the region, resulting from the existence of regional autonomy makes some regions in Indonesia are now beginning to optimize the government's performance in exploring the potential of tourism and one of them is Kabupaten Banyuwangi who managed to do development in tourism sector by exploiting local potency in banyuwangi city and tourism has changed the face of Banyuwangi as area which now become references of various government agencies in the country and other countries. It can be seen from the total number of tourists visiting the archipelago reached 3,831,703 people and foreign tourists as much as 78,865 people in 2016.The performance of banyuwangi government in the development of tourism in banyuwangi city can also be seen from the many awards that one of them received is 'The Best Festival City' by the tourism minister of RI for successfully promoting the city of banyuwangi and banyuwangi also became one of the cities that succeeded in developing the concept of tourism that is environmentally oriented tourism activities by prioritizing aspects of nature conservation, socio-cultural empowerment aspects, and local community economy as well as aspects of learning and education.